Criterion A of the DSM-5 Alternative Model for Personality Disorders in MMPI-2/RF Personality Disorder Scales - Waugh, Mark H.; Mulay, Abby L.; Crittenden, E. Bailey; Rossi, Gina (Frontiers in Psychology, 2021)
The Minnesota Multiphasic Personality Inventory (MMPI) instruments are frequently used to assess personality and psychopathology. Recent publications of personality disorder (PD) Spectra scales for dimensionalized PD syndromes with MMPI instruments may advance PD assessment. To this end, we examined MMPI-Second Edition (-2) and MMPI-2-Restructured Form (-RF) PD Spectra scales within the lens of a contemporary dimensional model of PDs, the Alternative Model for Personality Disorders (AMPD). The core dimension of PD, Criterion A of the AMPD or Level of Personality Functioning (LPF), was characterized quantitatively within the PD Spectra scales. By sequentially factor analyzing the scales of the Severity Indices of Personality Problems (SIPP-118) to a common general factor of PD, an index of LPF external to the MMPI item pool was established. This LPF dimension was strongly represented across most PD Spectra scales. LPF variance within the PD Spectra scales were deconstructed using measures of general demoralization (RCdemoralization) and maladaptive traits indexed by the Personality Psychopathology-5 (PSY-5). Nuanced LPF and PD Spectra scale relationships were discerned. Dimensionalized Antisocial PD, Borderline PD, Dependent PD, and Paranoid PD showed meaningful association with LPF after demoralization and maladaptive trait variances were removed. Examination of the MMPI-3 item pool shows the existing PD Spectra scale item sets are largely carried forward in the new edition of the MMPI. This suggests known PD Spectra scale correlates, including LPF relationships, may also pertain in the newest edition of the MMPI.